The Folk Healers in the Treatment Process for Paresis and Infertility - Mahama, Faisol; Bangopatae, Masufran; Asae, Khoreeyoh; Mohamad, Kanokkorn (Journal of Humanities and Social Sciences Nakhon Pathom Rajabhat University, 2024)
This qualitative research aimed to treatment process for paresis and infertility.The main informant was a folk healerin Patae sub-District, Yaha district, Yala province and the participants were 4 patients who received the treatment.The data were collected by interview with the interview method, then analyzed by the content analysis method. Results have shown that the folk healers can treat paresis and infertility, consisting of 3 processes: 1. Paresis 1.1 pre-treatment steps; praying for their medical teacher, diagnosis from history taking, symptoms and physical examination. 1.2 Procedure for treatment; using oil massage, the herbal compress, herbal bath and taking herbal for heart disease patients and 1.3 the post-treatment; advice on the patient’s behavior after treatment and 2. In infertile women, consisting of 2.1 Pre-treatment; praying for their medical teacher, physical examination and diagnosis. 2.2 Procedure for treatment; uterine lifting massage and rubs oil to the pelvic area. Taking herbal as single drugs and formulations drug. 2.3 the post-treatment; giving advice on practice, follow-up, visit patients 1 weekpertime for 3 weeks. The results can be integrated with public health in the area and to be an alternative for the people.